Ensuring Rapid Response Team Care Aligns With Patients' Limitations of Medical Therapy: A Quality Improvement Project. Issue 2 (12th April 2023) - Mininni, Nicolette C.; Whiteman, Kimberly; Stephens, Kimberly; George, Elisabeth; Swanson-Biearman, Brenda
Abstract : Background: Rapid response teams (RRTs) are designed to improve patient care during deterioration in clinical condition. Local Problem: Patients' desired limitations of medical therapy (LOMTs) were not documented or communicated to the RRT, and patients received care not aligned with their wishes. Methods: A multidisciplinary team developed a process for improving documentation, communication of LOMTs, and care delivery on 3 medical cardiology units. The team implemented 3 Plan-Do-Study-Act (PDSA) cycles over 6 months. Interventions: In cycle 1, team members taught the unit nurses, RRT members, and physicians to share LOMTs during handoff communications. Cycle 2 engaged case managers in LOMT documentation. In cycle 3, unit-based RRT simulation was conducted. Results: All care delivered by the RRT aligned with the documented LOMTs. Documentation of LOMTs increased from 76% to 82.5% ( P = .014). Conclusions: Education, scripting, and simulation were successful strategies to ensure that care given during RRT events aligned with patients' wishes.